Relationship between attachment styles and the resiliency amount of veterans wives - Z. akbari; T. vafaei; S. khosravi (Afarand Scholarly Publishing Institute, 2011)
Background: The resiliency of positive adaptation in response to adverse conditions and attachment styles and tend to approach people to establish a kind of close relationship with certain people and having a sense of security is allocated a special place in the area of family and mental health. Relationship between attachment styles and resiliency in the wives of veterans suffered the pressures are particularly important Purpose: Considering the existence of pressures and stresses in families of veterans, the purpose of this study to determine the relationship between resiliency and attachment styles of veterans wives. Materials and Methods: The method of research had been a correlation. Research sample was 60 Shiraz veterans spouses that have been selected systematic random manner. Data are collected from questionnaires resiliency CD-RIS, RAAS adult attachment styles and demographic characteristics were used. Results: for analyzing the Data it was used of correlation coefficients. Analysis revealed that there is a positive and significant relationship between secure attachment and the amount of resiliency (P<0.0001). There is a significant negative correlation between insecure attachment avoidance and the rate of resiliency (P< 0.001) there is no significant relationship between anxiety and insecure attachment level resiliency (P < 0.28). Conclusion: Based on the findings of this research it can be concluded that secure attachment is predictor the amount of resiliency and veterans spouses and who have this style have the more rates of resiliency. Spouses who have insecure avoidant attachment style have less amount of resiliency and insecure attachment styles anxiety have no effect on the amount of resiliency.